2017
DOI: 10.1016/j.jtcvs.2016.11.039
|View full text |Cite
|
Sign up to set email alerts
|

A score to estimate 30-day mortality after intensive care admission after cardiac surgery

Abstract: Preoperative and intraoperative variables can be used on admission to a cardiac surgical ICU to estimate 30-day mortality. The score could be used for risk stratification after cardiac surgery and evaluation of performance of cardiac surgical ICUs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Although some studies have stated that transfusion or RBC is an independent risk factor for mortality, others have shown that transfusion may play a secondary role and that other undetermined factors related to gender may also be important. 44,45…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have stated that transfusion or RBC is an independent risk factor for mortality, others have shown that transfusion may play a secondary role and that other undetermined factors related to gender may also be important. 44,45…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have stated that transfusion of RBC is an independent risk factor for mortality, others have shown that transfusion may play a secondary role and that other undetermined factors related to gender may be important. 44,45 In our study, patients who were smaller or anemic benefited more from AP than ANH in maintaining higher on-CPB hematocrits with lower transfusions.…”
Section: Discussionmentioning
confidence: 61%
“…Only recently, morbidity has been incorporated in these models as they provide a marker for the quality of life (53). So far, most risk scores for postoperative outcomes are based on preoperative inputs and lack incorporation of intraoperative variables to improve on performance (54).…”
Section: Postoperativementioning
confidence: 99%